Neo-economic doctrine of innovative economic transformation: digital, creative, and socio-ethical aspects of business - Dankevych, Andrii; Levchenko, Yuliia; Dankevych, Vitalii; Nitsenko, Vitalii; Ingram, Keisha Laraine (My University, 2025)
The global economy is dynamically evolving in the testing of digital tools for creating added value and maximizing profits. The new economic reality - neo-economics - involves a global reformatting of labor and capital markets and people's consciousness. Its philosophy includes digital innovations as a development tool, creativity as an economic force, ethics as a business norm, and sustainable development as the basis for the future. Changes encourage the concentration of scientific research on the issue of adaptation to new conditions. The research aimed to study the theoretical aspects of the formation of the doctrine of the concept of neo-economy as a systemic phenomenon and the ethics of its economic development. This requires understanding the paradigm of change (through the prism of digital, creative, and socio-ethical factors) and strengthening the dialogue on the concept of coexistence of market actors in the new digital reality. To achieve this goal, the following general scientific methods were used: analysis, synthesis, systematization, theoretical generalization, abstraction and analogy, induction, and forecasting. Results. The evolution of economic thought is studied. The need to find compromises in building a harmonious combination between economic growth and social values in the new reality is emphasized. The importance of human potential in the system of creative solutions of the global neo-economy and the need to develop levers to protect its ethical norms are revealed. The study's practical significance lies in the fact that it focuses society's attention on the issues of fundamental economic challenges (ethical, digital) and the search for ways to solve them. A new vision of humanity's role in the neo-economy paradigm is formulated. The definition of the concept of “neo-economy” based on the use of the creative component of human potential and the results of innovative activities (new technologies, innovations, information, knowledge) was suggested by the author. It is proposed to involve the broadest possible range of participants, namely “consumer-company-product- society-state,” in implementing new economic solutions to avoid social conflicts and build a humane symbiosis. The main conclusions can be used. The necessity of forming unified mechanisms for safeguarding ethical standards is substantiated. The need to expand the public dialogue of change is emphasized. Глобальна економіка динамічно еволюціонує в апробації цифрових інструментів формування доданої вартості та максимізації прибутку. Нова економічна реальність - нео- економіка передбачає глобальне переформатування як ринків праці і капіталу так і свідомості людей. В її філософії закладено цифрові інновації як інструмент розвитку; творчість як економічну силу; етику як норму ведення бізнесу; сталий розвиток як основу майбутнього. Зміни спонукають до концентрації наукових досліджень в питанні адаптації до нових умов. Метою статті є дослідження теоретичних аспектів становлення доктрини поняття нео-економіки, як системного явища та етики її економічного розвитку. Це вимагає осмислення парадигми змін (через призму цифрових, креативних та соціально-етичних чинників) та посилення діалогу щодо концепції спільного існування суб’єктів ринку в новій цифровій реальності. Для досягнення поставленої мети використано такі загальнонаукові методи: аналізу, синтезу, систематизації, теоретичного узагальнення, абстрагування та аналогії, індукції та прогнозування. Результати дослідження. Досліджено еволюцію економічної думки. Акцентовано на необхідності пошуку компромісів в побудові гармонійного поєднання між економічним зростанням та суспільними цінностями в новій реальності. Розкрито важливість людського потенціалу в системі креативних рішень глобальної нео-економіки та необхідності розробки важелів захисту його етичних норм. Практичне значення дослідження полягає в тому, що акцентовано увагу суспільства на проблематиці фундаментальних економічних викликів (етичних, цифрових) і пошуку шляхів їх вирішення. Сформульовано нове бачення ролі людства в парадигмі нео-економіка. Запропоновано власне визначення поняття «нео-економіка» на основі використання креативної складової людського потенціалу та результатів інноваційної діяльності (нових технологій, інновацій, інформації, знань). Запропоновано залучення якомога ширшого кола учасників а саме «споживач-компанія-продукт-суспільство-держава» в практику імплементації нових економічних рішень для уникнення соціальних конфліктів та побудови гуманного симбіозу. Основні висновки можуть бути використані. Обґрунтовано необхідності формування єдиних механізмів запобіжників дотримання етичних норм. Акцентовано необхідність розширення суспільного діалогу змін.
Keywords: кафедра економіки і права; creative economy; creative industries; digital economy; human potential; innovation; corporate social responsibility; investment portfolio; economist's ethics; social responsibility of business; artificial intelligence; neural networks; neural networks; креативна економіка; креативні індустрії; цифрова економіка; людський потенціал; інновації (економіка); корпоративна соціальна відповідальність; інвестиційний портфель; етика економіста; соціальна відповідальність бізнесу; штучний інтелект; нейромережі; innovation (economics)